2015
DOI: 10.1021/acsnano.5b05924
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Cleavage of Layered Carbon Nitride with Enhanced Photoluminescent Performances and Photoconduction

Abstract: Graphene quantum dots (GQDs) and carbon dots (C-dots) have various alluring properties and potential applications, but they are often limited by unsatisfied optical performance such as low quantum yield, ambiguous fluorescence emission mechanism, and narrow emission wavelength. Herein, we report that bulk polymeric carbon nitride could be utilized as a layered precursor to prepare carbon nitride nanostructures such as nanorods, nanoleaves and quantum dots by chemical tailoring. As doped carbon materials, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
214
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(226 citation statements)
references
References 65 publications
10
214
1
1
Order By: Relevance
“…The N 1s ( Figure 3d) signals for all samples can be deconvoluted into three peaks with binding energies of 398.7, 399.8 and 401.0 eV, which represent C-N=C (sp 2 hybridized nitrogen), tertiary nitrogen N-(C) 3 and C-N-H bond, respectively. 39,40 However, for O-g-C 3 N 4 monolayer sample, there is no clear XPS peak attributed to N-O bond at 402 eV. 41,42 The result indicated that in O-g-C 3 N 4 monolayer structure, there is no apparent N-O.…”
Section: Resultsmentioning
confidence: 99%
“…The N 1s ( Figure 3d) signals for all samples can be deconvoluted into three peaks with binding energies of 398.7, 399.8 and 401.0 eV, which represent C-N=C (sp 2 hybridized nitrogen), tertiary nitrogen N-(C) 3 and C-N-H bond, respectively. 39,40 However, for O-g-C 3 N 4 monolayer sample, there is no clear XPS peak attributed to N-O bond at 402 eV. 41,42 The result indicated that in O-g-C 3 N 4 monolayer structure, there is no apparent N-O.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that a variety of synthetic routes have been adopted to prepare CDs, and these approaches are generally classified into two categories – ‘‘top‐down’’ and ‘‘bottom‐up.” The former refers to the cutting of macroscopic carbon structures into CDs using physical or chemical methods, such as: bulk graphitic‐phase polymeric carbon nitride, graphite, and graphite oxide . As for the latter one, molecular precursors could be polymerized with each other to form dimer, oligomer and polymer via microwave synthesis, hydrothermal treatment, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…[50][51][52] Recently, we reported a general method to synthesize highly porous CN film from a supramolecular paste via a doctor-blade technique. [50][51][52] Recently, we reported a general method to synthesize highly porous CN film from a supramolecular paste via a doctor-blade technique.…”
mentioning
confidence: 99%